Low 15N Natural Abundance in Shoot Tissue of Brachiaria humidicola Is an Indicator of Reduced N Losses Due to Biological Nitrification Inhibition (BNI) - Karwat, Hannes; Egenolf, Konrad; Nuñez, Jonathan; Rao, Idupulapati M.; Rasche, Frank; Arango, Jacobo; Moreta, Danilo; Arévalo, Ashly; Cadisch, Georg (Frontiers Media, 2018)
The tropical forage grass Brachiaria humidicola (Bh) suppresses the activity of soil nitrifiers through biological nitrification inhibition (BNI). As a result, nitrate (NO−3) formation and leaching are reduced which is also expected to tighten the soil nitrogen (N) cycle. However, the beneficial relationship between reduced NO−3 losses and enhanced N uptake due to BNI has not been experimentally demonstrated yet. Nitrification discriminates against the 15N isotope and leads to 15N depleted NO−3, but 15N enriched NH+4 in soils. Leaching of 15N depleted NO−3 enriches the residual N pool in the soil with 15N. We hypothesized that altered nitrification and NO−3 leaching due to diverging BNI magnitudes in contrasting Bh genotypes influence soil 15N natural abundance (δ15N), which in turn is reflected in distinct δ15N in Bh shoot biomass. Consequently, high BNI was expected to be reflected in low plant δ15N of Bh. It was our objective to investigate under controlled conditions the link between shoot value of δ15N in several Bh genotypes and leached NO−3 amounts and shoot N uptake. Additionally, plant 15N and N% was monitored among a wide range of Bh genotypes with contrasting BNI potentials in field plots for 3 years. We measured leaf δ15N of young leaves (regrown after cutback) of Bh and combined it with nitrification rates (NRs) of incubated soil to test whether there is a direct relationship between plant δ15N and BNI. Increased leached NO−3 was positively correlated with higher δ15N in Bh, whereas the correlation between shoot N uptake and shoot δ15N was inverse. Field cultivation of a wide range of Bh genotypes over 3 years decreased NRs in incubated soil, while shoot δ15N declined and shoot N% increased over time. Leaf δ15N of Bh genotypes correlated positively with NRs of incubated soil. It was concluded that decreasing plant δ15N of Bh genotypes over time reflects the long-term effect of BNI as linked to lower NO−3 formation and reduced NO−3 leaching. Accordingly, a low δ15N in Bh shoot tissue verified its potential as indicator of high BNI activity of Bh genotypes.